Solve for y square root of 121+27^(9(48-y))=0

Math
121+279(48-y)=0
Simplify each term.
Tap for more steps…
Rewrite 121 as 112.
112+279(48-y)=0
Pull terms out from under the radical, assuming positive real numbers.
11+279(48-y)=0
Apply the distributive property.
11+279⋅48+9(-y)=0
Multiply 9 by 48.
11+27432+9(-y)=0
Multiply -1 by 9.
11+27432-9y=0
11+27432-9y=0
Subtract 11 from both sides of the equation.
27432-9y=-11
Take the natural logarithm of both sides of the equation to remove the variable from the exponent.
ln(27432-9y)=ln(-11)
The equation cannot be solved because ln(-11) is undefined.
Undefined
There is no solution for 27432-9y=-11
No solution
Solve for y square root of 121+27^(9(48-y))=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top